2016
DOI: 10.3389/fvets.2016.00102
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Generating and Maintaining Protective Vaccine-Induced Immune Responses for Foot-and-Mouth Disease Virus in Pigs

Abstract: Vaccination can play a central role in the control of outbreaks of foot-and-mouth disease (FMD) by reducing both the impact of clinical disease and the extent of virus transmission between susceptible animals. Recent incursions of exotic FMD virus lineages into several East Asian countries have highlighted the difficulties of generating and maintaining an adequate immune response in vaccinated pigs. Factors that impact vaccine performance include (i) the potency, antigenic payload, and formulation of a vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 83 publications
(88 reference statements)
0
27
0
Order By: Relevance
“…This risk plus other limitations, such as the need for a strict cold chain to preserve stability, and the use of updated vaccine strains, because of the high potential antigenic diversity of the virus, underlie the adoption of non-vaccination policies in FMDV-free countries, a controversial and by no means risk-free practice, as borne out by not infrequent outbreaks in those locations. In crisis scenarios of this kind [15], vaccines incorporating outbreak-relevant epitopes, eliciting protective responses and generated as a quick response to the epidemic, can become an invaluable emergency resource for FMD containment [16]. Among such emergency vaccines, those based on synthetic peptides [6] are particularly appealing because of their (i) total lack of biological hazard; (ii) possibility of displaying various epitopes on a single platform; (iii) DIVA compliance; (iv) efficient synthetic production and characterization as pharmaceuticals, and (v) no cold-chain required; easy transport and storage [17].…”
Section: Introductionmentioning
confidence: 99%
“…This risk plus other limitations, such as the need for a strict cold chain to preserve stability, and the use of updated vaccine strains, because of the high potential antigenic diversity of the virus, underlie the adoption of non-vaccination policies in FMDV-free countries, a controversial and by no means risk-free practice, as borne out by not infrequent outbreaks in those locations. In crisis scenarios of this kind [15], vaccines incorporating outbreak-relevant epitopes, eliciting protective responses and generated as a quick response to the epidemic, can become an invaluable emergency resource for FMD containment [16]. Among such emergency vaccines, those based on synthetic peptides [6] are particularly appealing because of their (i) total lack of biological hazard; (ii) possibility of displaying various epitopes on a single platform; (iii) DIVA compliance; (iv) efficient synthetic production and characterization as pharmaceuticals, and (v) no cold-chain required; easy transport and storage [17].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of a compulsory vaccination campaign, clinical disease has been reported in South Korea every year since 2014 [15 , WRLFMD reports; http://www.wrlfmd.org/ ] which raises questions about the effectiveness of vaccination in pigs. Amongst many possible reasons, a non-matching vaccine could be important [15] . Indeed vaccine matching work carried out at World Reference Laboratory (WRL), Pirbright using South Korean viruses from the years 2010 and 2011 indicated that only 60% (three out of five) of the isolates matched with O Manisa vaccine in-vitro [WRLFMD report; http://www.wrlfmd.org/ ].…”
Section: Introductionmentioning
confidence: 99%
“…Control programs include (1) removal sources of infection (pre-emptive culling, slaughtering), (2) preventing contact between infected and susceptible animals (restriction of animal and instrument movement), and (3) reduction in the proportion of susceptible animals (vaccination). Vaccination has been widely used to eradicate and control FMD due to its high effectiveness, especially when it is implemented together with other preventive tools [ 3 ].…”
mentioning
confidence: 99%
“…This circumstance has raise a question whether commercial FMD vaccine is really effective to control and prevent FMD outbreak in pigs. In this study, in order to exclude vaccine formulation-related factors for vaccine failure [ 3 ], we conducted the identification and quantification of vaccine strains in post-manufactured commercial vaccine and then evaluated immune response in the field.…”
mentioning
confidence: 99%